Aerodynamic optimization of vehicle shape and leading edge curvature for solar race car [electronic resource] - 183995 Mohammad Radzi Basir (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2008